2017
DOI: 10.29313/mimbar.v33i2.2849
|View full text |Cite
|
Sign up to set email alerts
|

A Therapeutic Communication Study of Families with Children Suffering from Cancer

Abstract: Therapeutic communication is a relatively new area of research in Indonesia. It is widely known that the success of therapeutic communication is largely influenced by the medical providers’ communication effectiveness when dealing with their clients. This paper reports on research that aimed to explore the connection between therapeutic communication and satisfaction and dissatisfaction as experienced by families of child cancer patients. It used a quantitative approach with a cross-sectional design. The sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on several existing studies, it was found that when health care providers listen to patients well, patients' devotion to treatment increases, patient satisfaction increases, and medical personnel are less likely to be subject to malpractice demands (Rahmawati et al, 2017). Moreover, the assessment of therapeutic communication by patients in the inpatients' room can vary from one ward to another.…”
Section: Resultsmentioning
confidence: 99%
“…Based on several existing studies, it was found that when health care providers listen to patients well, patients' devotion to treatment increases, patient satisfaction increases, and medical personnel are less likely to be subject to malpractice demands (Rahmawati et al, 2017). Moreover, the assessment of therapeutic communication by patients in the inpatients' room can vary from one ward to another.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the patient's point of view regarding the disease is very likely to be different from the doctor's understanding. Besides, the healthcare reality comprises biomedical, naturalistic, and personalistic systems, which overlap (Mulyana & Ganiem, 2021;Rahmawati et al, 2019). Patients and companions are also not always willing to openly explain their thoughts and feelings.…”
Section: Introductionmentioning
confidence: 99%